Keeping it simple: studying grammatical encoding with lexically reduced item sets - Veenstra, Alma; Acheson, Daniel J.; Meyer, Antje S. (Frontiers in Psychology, 2014)
Compared to the large body of work on lexical access, little research has been done on grammatical encoding in language production. An exception is the generation of subject-verb agreement. Here, two key findings have been reported: (1) Speakers make more agreement errors when the head and local noun of a phrase mismatch in number than when they match (e.g., the key to the cabinet(s)); and (2) this attraction effect is asymmetric, with stronger attraction for singular than for plural head nouns. Although these findings are robust, the cognitive processes leading to agreement errors and their significance for the generation of correct agreement are not fully understood. We propose that future studies of agreement, and grammatical encoding in general, may benefit from using paradigms that tightly control the variability of the lexical content of the material. We report two experiments illustrating this approach. In both of them, the experimental items featured combinations of four nouns, four color adjectives, and two prepositions. In Experiment 1, native speakers of Dutch described pictures in sentences such as the circle next to the stars is blue. In Experiment 2, they carried out a forced-choice task, where they read subject noun phrases (e.g., the circle next to the stars) and selected the correct verb-phrase (is blue or are blue) with a button press. Both experiments showed an attraction effect, with more errors after subject phrases with mismatching, compared to matching head and local nouns. This effect was stronger for singular than plural heads, replicating the attraction asymmetry. In contrast, the response times recorded in Experiment 2 showed similar attraction effects for singular and plural head nouns. These results demonstrate that critical agreement phenomena can be elicited reliably in lexically-reduced contexts. We discuss the theoretical implications of the findings and the potential and limitations of studies using lexically simple materials.